Hubungan Matriks Metaloproteinase-9 (MMP-9) Dengan Troponin-I (cTn-I) pada Infark Miokard dengan ST-Elevasi (STEMI) dan Sindrom Koroner Akut Tanpa ST-Elevasi (NSTEACS) - Budi Yuli Setianto; Indwiani Astuti; Bambang Irawan; Sofia Mubarika (Jurnal Kardiologi Indonesia, 2011)
Background: Acute coronary syndrome (ACS) is due to plaque rupture or erosion. Plaque rupture or erosion occurs because of the extra-cellular matrix destruction by an MMP (matrix metalloproteinase). Troponin I (cTn-I) is a biomarker that will increase in ACS with myocardial necrosis.Objective: To determine levels of MMP-9 difference between STEMI and NSTEACS and the relationship between levels of MMP-9 and cTn-I levels between the two groups.Methods: The sample examination performed in 80 patients with ACS (39 STEMI and 41 with NSTE-ACS) prior to the act of intravenous thrombolysis or coronary intervention.Analysis of MMP-9 levels relationship and cTn-I using Spearman test, and analysis of the cut-off relationship MMP-9 in the STEMI and NSTEACS groups were tested by Chi square.Results: Group STEMI had higher levels of MMP-9 and significantly higher compared with NSTE-ACS group (p = 0.002). Spearman correlation test showed a significant and positive correlation between MMP-9 and troponin-I between the two groups (p = 0.003 and r = 0.33).Conclusion: Increased levels of MMP-9 were significantly higher in STEMI compared with NSTE-ACS and its association with elevated levels of tro-ponin-I, provide information about the role of MMP-9 against the severity of heart muscle damage that occurred.